A Coherent Epistemological Theory in Management Philosophy Research - Wong, Edward Sek Khin; Chong, W.Y.; Wong, Y.M.; Choong, K.F. (American-Eurasian Network for Scientific Information, Jordan, 2011)
This article examines the coherent theory of management philosophy research. Drawing a conclusion for epistemology and ontology is an ambitious pursuit. The many schools of thought of epistemology and ontology are very well established, and they have strong and valid justifications for each. At the same time, these schools of thought also suffer from some inherent weaknesses to render them as falsehoods as well. Nevertheless, the importance of the deployment of epistemology and ontology in management research is undeniable. Researchers would be more reflexive if they could understand and comprehend the philosophical grounds before embarking on their journey to discover new knowledge. This paper provides an effective summary for novice researchers to acquire philosophical knowledge to be integrated in their studies or projects.